Syphilis and hepatitis B Co-infection among HIV-infected, sex-trafficked women and girls, Nepal. - Silverman, Jay G; Decke, Michele R; Gupta, Jhumka; Dharmadhikari, Ashwin; Seage, George R; Raj, Anita (Emerging infectious diseases, 2008)
Sex trafficking may play a major role in spread of HIV across South Asia. We investigated co-infection with HIV and other sexually transmitted diseases among 246 sex-trafficked women and girls from Nepal. Those who were HIV positive were more likely than those who were HIV negative to be infected with syphilis and/or hepatitis B.
Keywords: Adolescent; Adult; Female; Hepatitis B; HIV Infections; Humans; Nepal; Prevalence; Prostitution; Sex Offenses; Syphilis